Growth, Inequality, and Social Welfare Cross-Country Evidence - Dollar, David (The World Bank, 2014)
Social welfare functions that assign weights to individuals based on their income levels can be used to document the relative importance of growth and inequality changes for changes in social welfare. In a large panel of industrial and developing countries over the past 40 years, most of the cross-country and over-time variation in changes in social welfare is due to changes in average incomes. In contrast, the changes in inequality observed during this period are on average much smaller than changes in average incomes, are uncorrelated with changes in average incomes, and have contributed relatively little to changes in social welfare